2017
DOI: 10.1093/scan/nsx104
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral pattern separation and its link to the neural mechanisms of fear generalization

Abstract: Fear generalization is a prominent feature of anxiety disorders and post-traumatic stress disorder (PTSD). It is defined as enhanced fear responding to a stimulus that bears similarities, but is not identical to a threatening stimulus. Pattern separation, a hippocampal-dependent process, is critical for stimulus discrimination; it transforms similar experiences or events into non-overlapping representations. This study is the first in humans to investigate the extent to which fear generalization relies on beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 56 publications
3
54
0
Order By: Relevance
“…19,22 The dACC and anterior insula are known for their respective roles in the expression of fear responses 23 and interoceptive awareness, 24 with increasing activation along the similarity continu um to the CS. 25,26 The hippocampus and vmPFC have been implicated in stimulus discrimination and safety processing, 27,28 respectively, with decreasing activation along the similarity continuum. 25,26 Overall, the results therefore seem to indicate reduced threat-safety discrimination on a neural level in patients with anxiety and PTSD.…”
Section: J Psychiatry Neurosci 2019;44(3)mentioning
confidence: 99%
See 2 more Smart Citations
“…19,22 The dACC and anterior insula are known for their respective roles in the expression of fear responses 23 and interoceptive awareness, 24 with increasing activation along the similarity continu um to the CS. 25,26 The hippocampus and vmPFC have been implicated in stimulus discrimination and safety processing, 27,28 respectively, with decreasing activation along the similarity continuum. 25,26 Overall, the results therefore seem to indicate reduced threat-safety discrimination on a neural level in patients with anxiety and PTSD.…”
Section: J Psychiatry Neurosci 2019;44(3)mentioning
confidence: 99%
“…25,26 The hippocampus and vmPFC have been implicated in stimulus discrimination and safety processing, 27,28 respectively, with decreasing activation along the similarity continuum. 25,26 Overall, the results therefore seem to indicate reduced threat-safety discrimination on a neural level in patients with anxiety and PTSD. 19,22 Furthermore, generalization gradients in the vmPFC have been associated with symptoms of both anxiety and depression in those with GAD.…”
Section: J Psychiatry Neurosci 2019;44(3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Here we find that the present state of each individual brain, in terms of neural discrimination of stimuli, is predictive of the future generalization of fear in the subject. This suggests that a way to prevent generalization of dangerous and safe sounds is to improve neural discrimination of potentially threatening stimuli (Ginat-Frolich et al, 2017;Lange et al, 2017;Roesmann et al, 2020;Tuominen et al, 2019). Further work in this area can lead to a deeper understanding how genetic and social factors, as well early life experiences, shape cortical activity in this common and devastating disorder (Mahan and Ressler, 2012;Roesmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research utilizing a go/no go task measuring inhibitory processes reported that not only were patients with PTSD more likely to make inhibition-related errors than participants without trauma, but the process of inhibition relied on different brain networks such that controls relied on a right-lateralized cortical network while the PTSD participants activated only on the left-lateral frontal cortex during inhibition (Falconer et al, 2008). Additionally, recent research examining the relationship between fear generalization and behavioral pattern separation reports brain areas involved in inhibition and safety processing play a role in behavioral pattern separation including the subcallosal cortex, orbitofrontal cortex, and ventromedial prefrontal cortex (Lange et al, 2017). This is in line with recent work using rat models of PTSD which further implicate the prefrontal cortex as a key region leading to deficits in cognitive flexibility and inhibitory responses (George et al, 2015).…”
Section: Discussionmentioning
confidence: 99%